Multiple Buttress Reconstruction for Extended Total Maxillectomy by Mixed Use of Vascularized and Nonvascularized Fibula - Itaru Tsuge, MD, PhD; Hiroki Yamanaka, MD, PhD; Motoki Katsube, MD, PhD; Michiharu Sakamoto, MD, PhD; Naoki Morimoto, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Reconstruction of extended total maxillectomy is challenging. This study aimed to isolate the skull base from the nasal cavity to avoid intracranial infection, cerebrospinal fluid fistula, and palate closure to maintain feeding and conversation. However, facial appearance and symmetry are important for quality of life. We report primary multiple buttress reconstruction using a removed nonvascularized fibula that reduced the risk of infection and exposure. A 74-year-old woman experienced a local recurrence of right maxillary sinus cancer after subtotal maxillectomy and postoperative radiotherapy (60 Gy). We performed extended total maxillectomy, including the right eyeball, orbit, temporal bone, palate, and zygomatic arch. Primary reconstruction was performed using fibular and anterolateral thigh free flaps. The proximal fibula bone was resected to obtain the length of the peroneal vessels, and the distal 9 cm of the fibula was made into two pieces while keeping the peroneal vessels attached. The nonvascularized 5-cm fibula was split sagittally with an L-shaped section to maintain the strength of the fragments. An anterolateral thigh flap was elevated from the ipsilateral thigh attached to the partial vastus lateralis muscle, which was divided into proximal (to the cheek skin and prosthetic eye bed) and distal (to the nasal cavity and palate) skin islands. Two nonvascularized bone fragments were fixed at the lateral and infraorbital rims. The dead space around the built-up pillar made of transferred bone was filled with vastus lateralis muscle to prevent infection and depression. This approach allowed for one-stage multiple buttress reconstruction for extended total maxillectomy.